Local Climatological Data Summary: Effingham, Illinois, 1901-1990 - Bryan, Audrey A.; Armstrong, Wayne (Illinois State Water Survey, 1992)
Effingham (Effingham County) has a temperate continental climate, dominated by maritime tropical air from the Gulf of Mexico from about March through November. Gulf air generally supports relative humidities of about 60% during the day and 85% at night. During these months, there are occasional, brief interruptions of drier, cooler air from the Pacific Ocean, but typically only last for a few days. From November through March, the Effingham area is dominated by Pacific Ocean air. Four to six times each winter, cold, dry air from the Canadian Arctic breaks south, bringing temperatures into the teens and even units. The highest temperature on record is 111°F recorded both on 15 July 1936 and 14 July 1954, whereas the lowest is -29°F occurring on 24 January 1915. is peer reviewed Submitted by Agnes Stankiewicz (stankie2@illinois.edu) on 2014-10-29T14:43:20Z No. of bitstreams: 1 ISWSMP-98-8.pdf: 510575 bytes, checksum: 4cc2a336eaa2d002b6127fb3a6d8dabc (MD5) Made available in DSpace on 2014-10-29T14:43:20Z (GMT). No. of bitstreams: 1 ISWSMP-98-8.pdf: 510575 bytes, checksum: 4cc2a336eaa2d002b6127fb3a6d8dabc (MD5) Previous issue date: 1992 published or submitted for publication Open